2006
DOI: 10.1038/emm.2006.48
|View full text |Cite
|
Sign up to set email alerts
|

SP600125, a selective JNK inhibitor, aggravates hepatic ischemia-reperfusion injury

Abstract: Abstractc-Jun N-terminal kinase (JNK) is activated during hepatic reperfusion, and JNK inhibitors are known to protect other major organs from ischemia-reperfusion (I/R) injury. We attempted to determine the effect of SP600125, a JNK inhibitor, on hepatic I/R injury using a partial ischemia model in mice. Compared to a vehicle-treated group, the SP600125-treated group showed a greater increase in serum ALT levels 24 h after reperfusion with more severe parenchymal destruction and leukocyte infiltration. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…It was proposed that JNK had a pathological role in AILI in part by contributing to mitochondrial injury [14,21,35]. Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that JNK had a pathological role in AILI in part by contributing to mitochondrial injury [14,21,35]. Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Although JNK activation has been associated with liver IRI, its role in liver cell death or tissue inflammation remains controversial. 30,31 The ability of IR to induce JNK activation in CXCL10 KO mice indicates that it associates rather with the triggering event, that is, the initial ischemia-induced hepatocellular injury than the pro-inflammatory response per se. Conversely, the suppression of ERK activation suggests its role in liver inflammation further downstream IR cascade, that is, the inflammation-induced hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…7A). This rapid activation of JNK in RPH and NRPH participated in the acceleration of the liver regenerative response since injection of SP600125 before surgical procedure, a reversible inhibitor of JNK activity commonly used in the literature [4,[23][24][25][26] 18 h after resection. This response was correlated with low levels of Cyclin D1 and p21 Cip1 expression, the latter usually exhibiting a biphasic induction in mid-G1 and S-phase [21] (Fig.…”
Section: Acceleration Of the Liver Response Is Related To C-jun N-termentioning
confidence: 98%